Variation of weekly home range characteristics of Sumatran elephants (Elephas maximus sumatranus) in Bentang Seblat, Bengkulu Province, Indonesia - IRMA KUSUMA NINGRUM; YANTO SANTOSA; YUDI SETIAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Ningrum IK, Santosa Y, Setiawan Y. 2023. Variation of weekly home range characteristics of Sumatran elephants (Elephas maximus sumatranus) in Bentang Seblat, Bengkulu Province, Indonesia. Biodiversitas 24: 5854-5862. Bentang Seblat is one of the areas of conflict between Sumatran elephants and humans arising from space use problems because Sumatran elephants have specific preferences for habitat characteristics. This study aims to identify the characteristics of the weekly home range and analyze the relationship of weekly home range with habitat characteristics of Sumatran elephants in Bentang Seblat. GPS collar data from November 2020 until August 2022 were obtained from the Natural Resources Conservation Agency of Bengkulu-Lampung Province and habitat characteristics were obtained from Landsat 8 imagery. The data obtained were analyzed using chi-square test and Multiple Regression Analysis (MRA) with five variables: land cover, slope, distance from water sources, roads, and settlements. The results showed that the weekly home range was between 2.67 ha-239.98 ha, averaging 46.1 ha. The highest percentage of each habitat characteristic includes secondary forest (55.38%), flat slopes (59.01%), distances of 0-450 m from water sources (35.11%), distances of 0-400 m from roads (70.81%), and distances of 6-8 km from settlements (50.37%). The weekly home range is closely related to all habitat characteristics, with the highest level of relationship significance being the distance from water sources and the distance from the settlement.